The Role of Islamic Counseling Guidance in Preventing and Handling Bullying in College Students - Ulandari, Liyas; Mailin, Mailin (Madania: Jurnal Ilmu-Ilmu Keislaman, 2025)
This research aims to answer the main question of how the role of Islamic Guidance and Counseling (BPI) is in handling cases of bullying experienced by students at the Faculty of Da'wah and Communication, UIN Sumatera Utara. This study is motivated by the lack of Islamic value-based approaches in addressing psychological violence in higher education settings. The research uses a descriptive qualitative method with in-depth interviews, observation, and documentation techniques. The informants consisted of four people: one supervising lecturer and three students who had previously been victims of bullying and participated in BPI services. The data was analyzed using a thematic approach. The results show that the forms of bullying experienced include verbal, relational, and institutional, with psychological impacts such as stress, anxiety, and social withdrawal. BPI contributes to recovery through a spiritual approach based on the values of patience, trust in God, and self-purification, which is realized through mentoring, religious discussions, and character development. Although not yet supported by a strong institutional system, this service is considered practically beneficial in building students' mental resilience. The limitations of this study lie in the limited number of informants and the narrow scope of the study, so further research with a broader scope and stronger methodological design is recommended to strengthen the validity of the findings.